Effects of drought pretreatment on the morphology traits, biomass, and stoichiometric characteristics of the desert ephemeral plant - Liu, Qian; Li, Hongmin; Gong, Chen; Zhang, Qianli; Pan, Tao; Cao, Zhaodan; Chen, Yanfeng (Frontiers in Genetics, 2025)
Introduction: In the context of climate change, the frequency and intensity of droughts in arid and semi-arid areas have shown a substantially increasing trend, which inevitably affects plant survival and growth. However, it is unclear what survival and growth strategies plants subjected to drought pretreatment in the early life stages adopt when facing subsequent drought stress.Methods: Here, we conducted a field experiment and set up two treatments, control and drought pretreatment, to investigate the effects of drought pretreatment on the survival, phenology, morphology, biomass, and stoichiometric characteristics of the ephemeral plant Erodium oxyrhinchum in the Gurbantunggut Desert, China.Results: The results showed that the leafing, flowering, and fruiting stages under drought pretreatment occurred markedly earlier than the control treatment by 5.25 ± 1.2 d, 3.13 ± 0.84 d, and 4.75 ± 1.63 d, respectively. The life history of E. oxyrhinchum decreased 5 ± 1.38 d under drought pretreatment. Drought pretreatment accelerated seedling mortality, leading to a faster and earlier decline in survival percentage. The survival percentage of E. oxyrhinchum under drought pretreatment at the full blooming stage was approximately 18.59%, which was 5.19% higher than that of the control treatment. In addition, a positive correlation was observed between morphological traits and individual biomass, and drought pretreatment substantially increased individual biomass and reproductive output. For example, the reproductive biomass under drought pretreatment was 1.41 times than that of the control treatment during the full fruiting stage, indicating that plants subjected to drought pretreatment exhibited an overcompensation effect. Finally, from the perspective of stoichiometric characteristics, plants subjected to drought pretreatment require more phosphorus to enhance their resistance to severe drought.Conclusion: This study provides novel insights for the conservation and restoration of desert ecosystems in the context of climate change.